If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (x + 1) = -5 Reorder the terms: 2x + (1 + x) = -5 Remove parenthesis around (1 + x) 2x + 1 + x = -5 Reorder the terms: 1 + 2x + x = -5 Combine like terms: 2x + x = 3x 1 + 3x = -5 Solving 1 + 3x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = -5 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = -5 + -1 3x = -5 + -1 Combine like terms: -5 + -1 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 14+5x=7x | | f(x)=x^2+2x+2 | | 139-2x=25x+22 | | 12x+9=7x-3x-5 | | (-3)(2)(0)= | | 12(x-y)/-3 | | 16a-17=15 | | (3x+4y/5y)^3 | | 1y=5-3x | | 11-(2y-3)=0 | | p=b+3a+3Cforb | | 2x(3x+5)+x(6x-7)= | | 2.4q-3.7-3.9q=-2.5q-5.5 | | (4)(-2)(-3)= | | 2d+6=e | | x^2-21=-5 | | 25x^8-49= | | 6*16.4-7+4*16.4+23=180 | | x^2-21=5 | | (-6)(5)= | | x/-7=-8 | | x^4-121= | | X^2+14x-480=p | | 6+3+(-2)-1= | | 3x+10y=5 | | (5x^2y)(-2y^3)= | | 5*10+3+3*10+7=90 | | 3x^2+900x+120=0 | | x+9=5x-7 | | (X-a)*(x-7)=0 | | 4*7+17+6*7+3=90 | | X-9y=2 |